The Street as a Binding Factor : Measuring the Quality of Streets as Public Space within a Fragmenting City: The Case of Msasani Bonde la Mpunga, Dar es Salaam, Tanzania - Dayo-Babatunde, B. (CRC Press, 2020)
With this study we aim to measure the quality of streets as public spaces between various urban fragments – planned, gated and unplanned neighbourhoods – in a fragmented settlement located in Dar es Salaam, Tanzania. In contrast with the UN-Habitat (2013) study, in which only quantitative indicators were measured, our study measures the quality of streets by combining both quantitative (objective) indicators of street connectivity and qualitative (subjective) indicators based on residents’ perceptions. Results of this study are relevant for local planning authorities and policy-makers in areas of policy intervention and can contribute to filling the knowledge gap in the literature on African cities and their streets as binding factors.